Indução de estado de fluxo em aulas de performance musical: um estudo exploratório com estudantes instrumentistas de graduação - Abel Raimundo de Moraes Silva (2019)
This research aimed to investigate the possibilities of inducing flow states in classes and workshops of musical performance with instrumentalist students in undergraduate music programs at three universities in Minas Gerais, Brazil. The study was characterized as exploratory explanatory research in a naturalistic setting, employing a mixed model for data collection and analysis, adopting a pre-test and post-test intervention design without a control group. For the intervention, a protocol and a series of didactic strategies were developed to induce flow by enhancing the generation and regulation of musical performance by the subjects. A theoretical study on the correlation between the components of flow and the generative and regulatory processes of musical performance was undertaken as a basis for the development of these strategies. The research demonstrated the feasibility of inducing a state of flow in music performance classes through the application of the developed strategies. The flow components most sensitive to the strategies were loss of self-awareness, sense of control, autotelic experience, and immersion in action. The cognitive strategy that proved most effective was Anticipated Musical Listening and Partial Motor Control Abstention (AML-PMC), followed by self-confidence strategies: tolerance/resignification of error and abstention from external expectations. The primary contributions of this research include advancements in understanding the mechanisms of flow in musical performance, ways to increase its frequency, and its benefits. Consequently, more integrative didactic procedures for skills and attitudes, as well as more efficient mental techniques for deliberate practice and musical performance, can be developed. For music education, the research provides the opportunity to integrate the generated knowledge and the principles of flow theory into richer and more meaningful musical experiences in more stimulating environments for students. Considering that a pedagogy of flow would be a pedagogy of success and self-discovery, this approach could provide transformative experiences for any level and context of musical learning.